2018
DOI: 10.1021/acs.accounts.8b00292
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Nanoparticles versus Small Molecules: A Matter of Size

Abstract: The primary function of the cell membrane is to protect cells from their surroundings. This entails a strict regulation on controlling the exchange of matter between the cell and its environment. A key factor when considering potential biological applications of a particular chemical structure has to do with its ability to internalize into cells. Molecules that can readily cross cell membranes are frequently needed in biological research and medicine, since most therapeutic entities are designed to modulate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
242
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 346 publications
(264 citation statements)
references
References 60 publications
4
242
0
Order By: Relevance
“…For AuNP-based nanomedicines, the size and surface charges are important factors to determine their cellular uptake efficiency. 110,111 Circulating AuNPs with an enhanced permeability and retention (EPR) effect benets their selective accumulation at tumour sites. Cellular uptake of AuNPs with strongly negatively charged surface is very hard.…”
Section: Functionalized-aunps For Cancer Therapymentioning
confidence: 99%
“…For AuNP-based nanomedicines, the size and surface charges are important factors to determine their cellular uptake efficiency. 110,111 Circulating AuNPs with an enhanced permeability and retention (EPR) effect benets their selective accumulation at tumour sites. Cellular uptake of AuNPs with strongly negatively charged surface is very hard.…”
Section: Functionalized-aunps For Cancer Therapymentioning
confidence: 99%
“…Our data also showed that the cellular uptake was key for the activity of either types of CDs. The crosslinked CDs were mainly taken up via an energy-dependent process (likely endocytosis), which could be expected considering that their large molecular weight would hamper their diffusion through the cell membrane [52]. In contrast, the fact that monomeric HPβCD uptake was only reduced at 4 °C and not under energy depleting conditions would support the theory that a diffusive process might be involved [53].…”
Section: Discussionmentioning
confidence: 86%
“…It has been well-documented that nanoprobes often accumulated in lysosomes via the interplay of size and surface charge: (1) nanostructure could be taken up by cells by the energy-dependent endocytosis pathway whose destination is lysosomes; 65,66 (2) the positively charged amino moiety enables the nanoparticles to enter into lysosomes. 45,58,67,68 To inspect the subcellular targeting ability of DTFN, HeLa cells pre-treated with DTFN were co-incubated with Lyso-Tracker Red and Mito-Tracker Red, respectively. As displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%